Finite elements in convection dominated flows: a semi-Lagrangian method. - Silva, Hugo Marcial Checo (2021)
Submitted by Boris Flegr (boris@uerj.br) on 2021-01-06T19:13:04Z No. of bitstreams: 4 Hugo Marcial Checo Silva 1.pdf: 1161380 bytes, checksum: cc1d5e17c0118413ddcfca54661ce8af (MD5) Hugo Marcial Checo Silva 2.pdf: 2690861 bytes, checksum: 234acd814b57b2da3878aaabb22b3409 (MD5) Hugo Marcial Checo Silva 3.pdf: 7600536 bytes, checksum: 5200d53b00f3fd1387cb70d97d8caff7 (MD5) Hugo Marcial Checo Silva 4.pdf: 1418081 bytes, checksum: 5242a87f2d60fb2fb0da6c0f3cd83e24 (MD5)